2017
DOI: 10.1515/intag-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Physical parameters of Fluvisols on flooded and non-flooded terraces

Abstract: The heterogeneity of soil physical properties of Fluvisols, lack of large pristine areas, and different moisture regimes on non-flooded and flooded terraces impede the possibility to find a soil profile which can serve as a baseline for estimating the impact of natural or anthropogenic factors on soil evolution. The aim of this study is to compare the pore size distribution of pristine Fluvisols on flooded and non-flooded terraces using the method of the soil water retention curve, mercury intrusion porosimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Notable is a large difference between the soil density of the uppermost 30 cm and the depth from 40 cm, where soil bulk density was from 1.41 to 1.54 g cm −3 ) (Figure 3). Soil bulk density of the upper 30 cm exceeds values, commonly found in the soils of alluvial plains (Kercheva et al, 2017). These results confirm the findings from the field, namely that the uppermost soil layer is highly compacted, hindering the flow of water to depth.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Notable is a large difference between the soil density of the uppermost 30 cm and the depth from 40 cm, where soil bulk density was from 1.41 to 1.54 g cm −3 ) (Figure 3). Soil bulk density of the upper 30 cm exceeds values, commonly found in the soils of alluvial plains (Kercheva et al, 2017). These results confirm the findings from the field, namely that the uppermost soil layer is highly compacted, hindering the flow of water to depth.…”
Section: Resultssupporting
confidence: 89%
“…by higher hydraulic conductivities ranging from 2 to 180 m day -1 in the subsoil) compared to upper laying parts of the watershed (Miller et al, 2016;Šípek et al, 2019). Soils are usually enriched with nutrients and characterized by high vertical and horizontal heterogeneity, which is explained with the varying characteristics of alluvial sediments, regime of deposition, age of formation (distance to the river), and land use (Kercheva et al, 2017). In some cases, Fluvisols may be subjected to contamination of deposits (Antić et al, 2006;Schwartz et al, 2006;Mabit et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although many authors reported the transformation of drained alluvial soils towards the development of mollic or cambic horizons, which excluded these soils from Fluvisols group according to the statements of WRB classification, Fluvisols are still reported from regulated and drained valleys [10][11][12]32,54,55]. This may indicate that many authors still apply the term "Fluvisols" as a synonym of alluvial soils on the Holocene river terraces, irrespective of the actual stage of their pedogenic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important factors in the variability of valley and/or floodplain ecosystems are soils composed of spatially and vertically differentiated alluvial sediments [6][7][8]. Sedimentation conditions can significantly change over time; therefore, stratification is a basic feature of valley/floodplain soils, affecting their physicochemical and water properties, as well as the productivity of alluvial soils [9][10][11][12]. Moreover, the sequences of sediment layers and soil horizons in the soil profiles on floodplain terraces demonstrate the successions of stable periods with distinct pedogenesis and unstable (i.e., geomorphologically active) periods, in which fresh alluvial layers were accumulated [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…Unsaturated hydraulic conductivities can also vary widely-from about 50 cm/day up to less than 1 × 10 -32 cm/day, depending on the level of saturation. Kercheva et al [56] reported similar hydraulic soil properties in the Fluvisols. In Profile 1 (Figure 3, Table 5), it can be seen that the impermeable boundary is reached when the water content is 0.16 and 0.18, and the effective saturation is between 29% and 41%.…”
Section: Relationships Between the Soil Hydraulic Datamentioning
confidence: 73%